2018
DOI: 10.1101/449298
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Novel diversity within marine Mamiellophyceae (Chlorophyta) unveiled by metabarcoding

Abstract: The Ocean Sampling Day (OSD) project provided metabarcoding data for the V4 hyper-variable regions of the 18S rRNA gene from 157 samples collected at 143 mostly coastal stations. In this paper we focus on the class Mamiellophyceae, which was found at nearly all OSD stations and represented 55 % of the green microalgae (Chlorophyta) reads in the 2014 OSD dataset. We performed phylogenetic analyses of unique OSD metabarcodes (ASV, amplicon single variants) and reference GenBank sequences from cultures and from t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 66 publications
1
4
1
Order By: Relevance
“…While Chlorophyta showed relatively high % values with microscopy, with HTS they were rarely detected and with a low % sequence abundance. The discrepancy in the detection of Chlorophyta in a freshwater lake (this study) with respect to marine waters (Tragin et al, 2018; Tragin & Vaulot, 2019) might indicate that the efficiency of HTS for Chlorophyta can be habitat dependent. Dinophyta and Eustigmatophyta showed the odd situation of a higher diversity but a lower % abundance with HTS compared to microscopy.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…While Chlorophyta showed relatively high % values with microscopy, with HTS they were rarely detected and with a low % sequence abundance. The discrepancy in the detection of Chlorophyta in a freshwater lake (this study) with respect to marine waters (Tragin et al, 2018; Tragin & Vaulot, 2019) might indicate that the efficiency of HTS for Chlorophyta can be habitat dependent. Dinophyta and Eustigmatophyta showed the odd situation of a higher diversity but a lower % abundance with HTS compared to microscopy.…”
Section: Discussioncontrasting
confidence: 54%
“…Despite the higher richness of Charophyta reported with microscopy, microscopy and HTS data showed similarly low % values (generally <2%), corroborating that this phylum was a rare component of the phytoplankton community. For Chlorophyta, tufA (Vieira et al, 2016) or a combination of different primers should be used (Marcelino & Verbruggen, 2016); however, the V4 region of the 18S rRNA reveals a vast diversity of Chlorophyta in marine waters (Tragin, Zingone, & Vaulot, 2018; Tragin & Vaulot, 2019). While Chlorophyta showed relatively high % values with microscopy, with HTS they were rarely detected and with a low % sequence abundance.…”
Section: Discussionmentioning
confidence: 99%
“…Eukaryotes in the estuary were dominated (in terms of relative abundance) by Bacillariophyta, Mamiellophyceae, and Dinophyceae, consistent with other coastal 18S barcoding studies (Massana et al, 2015;Tragin et al, 2018;Gong et al, 2020). These protist groups (and many others) are functionally and phylogenetically diverse (Caron et al, 2012;Tragin and Vaulot, 2019), which may explain why we observed little fluctuation in class level relative abundance with temperature. Diatoms are known to exhibit species-specific temperature-growth relationships and occupy thermally driven environmental niches (Canesi and Rynearson, 2016;Rynearson et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…However, metatranscriptomic data from surface waters unveiled that the dominating species was O. lucimarinus. A previous study has shown that this species inhabits waters from the surface to the DCM (Rodríguez et al, 2005) and it is the most widely distributed, whereas O. tauri and O. mediterraneus are mostly restricted to the surface layer of coastal waters and lagoons (Rodríguez et al, 2005;Tragin and Vaulot, 2019). Thus, it is likely that most Ostreococcus cells found in our samples belonged to O. lucimarinus.…”
Section: Discussionmentioning
confidence: 75%
“…Ostreococcus (Mamiellaceae) is the world's smallest free-living eukaryote known, with a cell diameter of $1 μm (Courties et al, 1994;Derelle et al, 2006;Sanchez et al, 2019). The genus comprises several species that can be ubiquitously found from the coast to the open ocean, and from mesotrophic to oligotrophic waters (Demir-Hilton et al, 2011;Tragin and Vaulot, 2019). The number of sequenced Ostreococcus viruses is constantly increasing, and nowadays the complete genomes of many Ostreococcus viruses are available (e.g.…”
Section: Introductionmentioning
confidence: 99%